Ethos discursivo e (re)construção da linguagem: do jornalismo on-line para as páginas do Facebook - Candido, Ingrid Caroline Albuquerque [UNIFESP] (2019)
Based on studies of French Discourse Analysis, this dissertation aims to analyze in what extent the different linguistic-discursive constructions reflect different positions, which resignify the perspective of the enunciators. By this bias, for this investigation were found two media that hold great social importance: social networks and online newspapers. The corpus selected for analysis is divided into two parts: nine posts from the Caneta Desmanipuladora profile of the social network Facebook, which deal with revisions and interventions in journalistic headlines, and in the same nine headlines, as published by the online newspapers, these being Folha de S.Paulo, O Globo and O Estado de S.Paulo, totalizing the reflection on eighteen statements that are observed before and after the interventions of the page. All the headlines of the selected newspapers deal with news published in the context of the government of interim president Michel Temer, reported in the period from 05/24/2016 until 08/31/2016, considering Brazil‘s constant political and social changes at this time, when Dilma Rousseff‘s impeachment process was is transit. The study of the selected corpus is justified by the importance of online communication in contemporaneity, allowing us to glimpse the position disparities concerning a huge variety of levels, political period which Brasil was going through. The theoretical concepts selected for this dissertation are based on Maingueneau's (1997; 2004; 2006; 2008 a; 2008b; 2010; 2011; 2014 a; 2014 b; 2015), studies, especially the definitions of discourse, discursive ethos and interdiscursivity. It is believed study lead the reader into a linguistic-discursive resources reflection that demarcate positions, re-meaning the statements depending on the subjects they enunciate.